2014
DOI: 10.1103/physrevd.89.034001
|View full text |Cite
|
Sign up to set email alerts
|

Y(4260): Hadronic molecule versus hadro-charmonium interpretation

Abstract: In this paper we confront both the hadronic molecule and the hadro-charmonium interpretations of the Y (4260) with the experimental data currently available. We conclude that the data support the Y (4260) being dominantly a D1D + c.c. hadronic molecule while they challenge the hadrocharmonium interpretation. However, additional data is necessary to allow for stronger conclusions. The Z c (3900) was soon confirmed by the Belle Collaboration [6] and an analysis based on the CLEO-c data [7].In Ref.[8], it was arg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 49 publications
5
75
0
Order By: Relevance
“…It should be addressed that the compact cc in an S wave should decouple to theDD 1 + c.c. molecular component in the HQSS limit [22,24,26,27]. However, since the charm quark is not heavy enough the HQSS breaking is anticipated and there will be several possible mechanisms leading to mixing between the compact cc and molecularDD 1 + c.c.…”
Section: The Line Shapes Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be addressed that the compact cc in an S wave should decouple to theDD 1 + c.c. molecular component in the HQSS limit [22,24,26,27]. However, since the charm quark is not heavy enough the HQSS breaking is anticipated and there will be several possible mechanisms leading to mixing between the compact cc and molecularDD 1 + c.c.…”
Section: The Line Shapes Ofmentioning
confidence: 99%
“…However, as shown by Refs. [26,27], the HQSS breaking in the charmonium mass region should be expected and it is sufficient to account for the cross sections observed for Y (4260). Our studies in this work will further clarify the HQSS breaking effects and make the molecular picture dynamically self-contained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a series of recent works it was shown that theDD 1 (2420) + c.c. molecular scenario is favored by the study of cross section lineshapes in those exclusive channels [27][28][29][30][31][32]36]. In particular, the nature of Y(4260) as theDD 1 (2420) + c.c.…”
Section: Nature Of Y(4260) and Production Of Z C (3900) In Y(4260) → mentioning
confidence: 99%
“…However, as shown by Ref. [12], the heavy quark spin symmetry breaking in the charmonium mass region cannot be neglected and the production rate for D-wave charmonium vectors have been an indication of the heavy quark spin symmetry breaking strength. In the production of Y(4260) the presence of a small cc component is a natural measure of the heavy quark spin symmetry breaking scale, which can be extracted in our framework by implementing Weinberg's compositeness theorem [13,14].…”
Section: Introductionmentioning
confidence: 99%